Digitalization of Islamic Religious Education Practices in Junior High Schools - Selvia Dwi Puspita; Lety Febriana; Rifa'i Rifa'i; Syukri Amin (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: Digitalization of Islamic Religious Education Practices in Junior High SchoolsObjective: This study aims to analyse the forms of digitalisation access gaps in Islamic education, identify contributing factors, and formulate strategic solutions to overcome these limitations. Method: This study uses a qualitative, descriptive design. Data were collected through participatory observation, in-depth interviews with school principals, Islamic education teachers, and students, and documentation. Data analysis used the Miles and Huberman interactive model. Results: There are three main dimensions of digital access gaps: infrastructure access gaps include unstable internet connectivity and an unfavourable device ratio; socio-economic access gaps reflect disparities in digital device ownership; and competency access gaps reveal Islamic education teachers' limited digital literacy in integrating technology into daily learning. Conclusion: The digital access gap creates digital stratification in Islamic education, potentially affecting the equality of learning opportunities for students. Contribution: This study provides evidence-based recommendations for strategic policies to achieve equitable digital access in suburban schools, particularly in Islamic education, which has unique characteristics in character and spiritual development. INDONESIAN: Digitalisasi Praktik Pembelajaran Pendidikan Agama Islam di SMPTujuan: Penelitian ini bertujuan untuk menganalisis bentuk kesenjangan akses digitalisasi dalam pembelajaran PAI, mengidentifikasi faktor-faktor penyebab, dan merumuskan solusi strategis untuk mengatasi keterbatasan tersebut. Metode: Penelitian ini menggunakan pendekatan kualitatif dengan desain deskriptif. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam dengan kepala sekolah, guru PAI, dan siswa, serta dokumentasi. Analisis data menggunakan model interaktif Miles and Huberman. Hasil: Terdapat tiga dimensi utama kesenjangan akses digital: kesenjangan akses infrastruktur meliputi konektivitas internet tidak stabil dan rasio perangkat yang belum ideal, kesenjangan akses berbasis sosial-ekonomi mencerminkan disparitas kepemilikan perangkat digital, dan kesenjangan akses kompetensi menunjukkan keterbatasan literasi digital guru PAI dalam mengintegrasikan teknologi ke dalam pembelajaran sehari-hari. Kesimpulan: Kesenjangan akses digitalmenciptakan stratifikasi digital dalam pembelajaran PAI yang berpotensi mempengaruhi kesetaraan kesempatan belajar siswa. Kontribusi: Penelitian ini memberikan rekomendasi berbasis bukti untuk kebijakan strategis guna mencapai pemerataan akses digital di sekolah pinggiran, khususnya dalam pembelajaran PAI yang memiliki karakteristik unik dalam pembentukan karakter dan spiritualitas